Comportamento epidemiológico dos acidentes ofídico no Departamento de Magdalena, Colômbia (2009-2013)] [Comportamiento epidemiológico del accidente ofídico en el Departamento del Magdalena, Colombia (2009-2013) (2016)
Objective: To determine the epidemiological behavior of snakebite accidents in the Department of Magdalena, in the years between 2009 and 2013. Materials and methods: Descriptive and retrospective study. The sample size was 485 cases reported to the national Public Health Surveillance System. The information was organized in Microsoft Excel® and processed in Epi-INFO® program version 3.5.4 of 2012. Bivariate analysis was performed using descriptive statistics, association test (OR) and statistical significance (p <0.05); keeping the corresponding ethical and methodological rigor. Results: The age group between 10 and 29 years was the most affected (44.5 %), predominantly males (73 %) living in rural areas (59 %). The municipalities with the highest incidence and reporting cases were zona bananera (15.9 %), Ciénaga (11.8 %), El Banco (10.7 %), Pivijay (9.5%) and Ariguaní (8.2 %). We found statistical association between being bitten by mapana snake and exerting both agricultural work: OR = 0.53 (CI95 %: 0.36 - 0.77; p = 0.00116) and housework: OR = 2.29 (CI95 %: 1.36 - 3.87; p = 0.00148). It appears similar between being bitten by a mapana snake and having nausea: OR = 1.60 (CI95 %: 1.04 - 2.44; p = 0.029) as systemic clinical manifestations. Conclusions: The snakebites continue to be events of interest to global public health. However, it is necessary to encourage adherence to the national epidemiological surveillance protocol and to improve notification in the primary institutions to avoid underreporting. Moreover, it is important to continue the research in different regions in order to compare findings and to establish prevention and control strategies. © 2016, Universidad del Rosario. All rights reserved.